AN OVERVIEW OF THE HISTORY OF MATHEMATICAL THOUGHT (International Educators Conference, 2025)
The article scientifically analyzes the process of historical formation of mathematical thinking, its roots and stages of development. The system of mathematical knowledge, which began with practical calculation methods in ancient Egyptian, Mesopotamia, Indian and Chinese civilizations, later gained a logical and scientific basis through the theoretical methods of Greek scientists, especially Euclid.At the same time, it is emphasized that the scientific legacy of Central Asian scholars during the Islamic Renaissance - Al-Khwarizmi, Al-Biruni, Omar Khayyam, and Nasir al-Din al-Tusi - raised mathematical thinking to a new level.The role of women in science and their achievements in the field of mathematical analysis are highlighted using the work of Sofia Kovalevskaya in the 19th century. The development of mathematics in modern times, in close connection with the fields of information technology, artificial intelligence, and analysis, is also analyzed.The article presents scientific and philosophical conclusions about the role of mathematical thought in human thinking and spiritual development.